Trusted edge computing for smart healthcare - Shaoliang PENG; Liang BAI; Li WANG; Minxia CHENG; Shulin WANG (Dianxin kexue)
With the rapid development of internet of things technology,in order to better develop modern medicine,avoid the “isolated” crisis of information,and meet the requirements of timeliness and computing performance of massive data generated by edge devices,it is a new trend of the times to combine edge computing with smart healthcare treatment.However,edge computing has a certain degree of openness,and it is prone to potential safety hazards.Therefore,people pay more and more attention to the security and privacy protection of edge computing system for smart healthcare treatment.The edge computing system and its architecture for smart healthcare were introduced,and the security risks encountered by smart healthcare in edge computing was explained,and some scholars’ solutions to the security risks were introduced.Finally,a security framework,and specific solutions for security and privacy protection under the framework were put forward,which providing some help for the trusted research of smart healthcare edge computing.